2022
DOI: 10.4039/tce.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Reduced avian predation on an ultraviolet-fluorescing caterpillar model

Abstract: Many caterpillars exhibit patterns of ultraviolet (UV) fluorescence, although its purpose is unclear. We used realistic plasticine models of a fluorescing caterpillar species, the Polyphemus moth, Antheraea polyphemus (Lepidoptera; Saturniidae), adorned with fluorescent paint treatments and unpainted controls to quantify bird predation in two hardwood forested regions of New York State, United States of America. In separate field studies, significantly more birds struck deployed model caterpillars that had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Pynne et al (2021) also suggested camouflage against an unspecified background for pocket gophers (Geomyidae), citing soil photoluminescence as a possible source of luminophores. Photoluminescence may also act as aposematism, as suggested for caterpillars (Antheraea polyphemus) (Czarnecki et al 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Pynne et al (2021) also suggested camouflage against an unspecified background for pocket gophers (Geomyidae), citing soil photoluminescence as a possible source of luminophores. Photoluminescence may also act as aposematism, as suggested for caterpillars (Antheraea polyphemus) (Czarnecki et al 2022).…”
Section: Introductionmentioning
confidence: 97%
“…[22,17] Fluorescence may function as another mechanism to deter or avoid predation. [23] Moreover, the fluorescence in butterflies has been found to be directional, due to their nanostructured wings. [24] Discovering new fluorescent molecules in the living world is technologically important, as they can find applications in biosensors, organic photovoltaics, organic lasers, organic light emitting diodes, VCSEL diodes, security inks, dyes, and labels for anti-counterfeiting measures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Third, and perhaps most importantly, I have not considered the visual system of the receiver and the fact that some predators can perceive UV wavelengths. Many caterpillars, including Bombycoidea, fluoresce under UV light (Czarnecki et al, 2022), which may serve to increase contrast or distort their shape. My assessment of camouflage is then likely an overestimate, as some species may be more contrasting to some predators (Medina et al, 2020).…”
Section: Morphological Assessmentmentioning
confidence: 99%